'Bridging the Sexes': Feelings, Professional Communities and Emotional Practices in the Spanish Intersex Clinic. (1st October 2020) - Fernández-Garrido, Sam; Medina-Domenech, Rosa M.
ABSTRACT: Health professionals' emotions in the Spanish Intersex Clinic (SIC) act as structures of feeling, not easily available for analysis. Then, what is their role in configuring clinical judgments and decisions regarding non-binary bodies? Non-crystallized structures of feeling emerge as shared practices by the professional community. These practices allow them to square their expectations of a de-emotionalized clinical objectivity and to relieve a distress allegedly caused by a corporeal difference, and not by a sex/gender system that has a hard time processing embodied diversities. In their emotional practices of (un)bridging the (dichotomy of) sexes in the SIC, clinicians emotionally activate (handling fear and uncertainty, showing empathy, using emotionally evocative images), and also emotionally deactivate narratives of sexual difference (using insipid terminology, overusing technical jargon, managing information mechanically, or through acts of debarring to avoid emotions). Emotional practices play a decisive role in interconnecting and shaping ways of doing (strategies, techniques, values) with entities (body, artifacts), to put into practice the knowledge systems that place the human body inside a sexual binary. To envision a language for these practices can bring awareness of the role played by emotions. More importantly, it can facilitate taking into consideration the agency of patients, including possible non binary decisions about their bodies.